C1-Symmetric [Ir(C^N1)(C^N2)(N^O)]-tris-heteroleptic Ir(iii)-complexes with a horizontal orientation for efficient near-infrared (NIR) polymer light-emitting diodes (PLEDs). Issue 26 (21st June 2021) - Li, Wentao; Miao, Tiezheng; Wang, Baowen; Liu, Jiaxiang; Lü, Xingqiang; Fu, Guorui; Feng, Weixu; Wong, Wai-Yeung
Abstract : Through doping of the [Ir(C^N 1 )(C^N 2 )(N^O)]-tris-heteroleptic Ir(iii )-complex [Ir(iqbt)(ppy)(pic)] (1 ) or [Ir(iqbt)(ppy)(Br-pic)] (2 ) into the EML, the preferentially horizontal orientation is beneficial for their high-performance NIR-PLEDs. Abstract : Using conventional fac -[Ir(C^N)3 ]-homoleptic or [Ir(C^N)2 (L^X)]-bis-heteroleptic iridium(iii )-complexes with NIR-phosphorescence (NIR = near infrared) as dopants, the realization of reliable NIR-OLEDs/PLEDs (organic/polymer light-emitting diodes) with high performance remains a real challenge. In this study, taking Hqibt (1-(benzo[ b ]-thiophen-2-yl)-isoquinoline) as the HC^N 1 ligand, Hppy (phenyl-4-yl)pyridine) as the HC^N 2 ligand and Br-Hpic (5-Br-picolinic acid) or Hpic (picolinic acid) as the N^O-ancillary, two novel C 1 -symmetric [Ir(C^N 1 )(C^N 2 )(N^O)]-tris-heteroleptic iridium(iii )-complexes [Ir(iqbt)(ppy)(pic)] (1 ) and [Ir(iqbt)(ppy)(Br-pic)] (2 ) are molecularly designed, respectively, where large TDM (transition dipole moment) and strengthened 3 MLCT (metal-to-ligand charge transfer) effects are established to afford their good NIR-phosphorescent efficiency ( Φ PL = 0.27 for 1 ( λ em = 698 nm); 0.21 for 2 ( λ em = 696 nm)). Moreover, in their doped EMLs (emitting layers), a preferentially horizontal orientation of the TDMs is promoted, due to which, the NIR-PLEDs-1–2 exhibit an attractively high efficiency ( η maxEQE = 3.1–4.7%; λ em = 698 nm) as well as an almost negligible (<5%) efficiency roll-off. This finding means the C 1 -symmetric [Ir(C^N 1 )(C^N 2 )(N^O)]-tris-heteroleptic Ir(iii )-complexes show potential as low-cost, large-area and scalable NIR-PLEDs.